Insight into disinfection byproduct formation potential of aged biochar and its effects during chlorination. (1st September 2022) - Yang, Hailan; Ye, Shujing; Wang, Han; Zhou, Chengyun; Xiong, Ting; Deng, Yuanyuan; Fu, Qianmin; Zeng, Guangming; Zeng, Zhuotong; Tan, Xiaofei
Abstract: Biochar can achieve multiple benefits including solid waste management, polluted water remediation, carbon sequestration, and emission reduction. However, various environmental factors (such as temperature variations and dry-wet alternation) and microbial activity may lead to the fragmentation, dissolution, and oxidation of biochar. These accelerate the dissolution of biochar-derived dissolved organic matter (DOM) and then influence disinfection byproducts formation potential (DBPFP) throughout the water treatment process. In this paper, biochars from six biomass feedstocks with five aging processes were prepared, and the DBPFP of biochar and its derived DOM were first studied systematically. Different aging processes might increase the DBPFP of biochar by increasing DOM content and changing the fraction distribution of DOM derived from biochar. Especially, the DBPFP of biochar increased apparently with the chemical aging process. Coexisting with the environmental concentration of humic acid, even aged biochar showed the potential to reduce DBPFP and integrated toxic risk value of the mixed system. In this study, the DBPFP of biochar-derived DOM during the disinfection process is confirmed, and the results can give information to the selection of biomass feedstocks of biochar and its service life in the water treatment process. Graphical abstract: Image 1 Highlights: Disinfection byproducts formation potential of aged biochar was first evaluated. DBPFP of biochar influenced by feedstocks and pyrolysis temperature. ITRV of chemical aged biochar-derived DBPs increased by 100 times. Even aged biochar can reduce toxicity of simulated raw water during chlorination.